Investigating Rain Attenuation Models for Satellite Links in Tropical Nigeria - Abayomi Isiaka O. Yussuff; Ibukun E Koleoso; Nor Hisham Haji Khamis (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2018)
The analyses of rain models for satellite communication links of Ku and Ka bands in Lagos, Nigeria is the focus of this paper. The choice of these frequency bands was informed by the acknowledged fact that satellite signal fading and outages are predominant at those bands. The ITU-R P. 618-12 is the globally adopted prediction model; temperate, equatorial and tropical regions, inclusive. However, there was need to review the suitability of this model especially as it concerned equatorial and tropical stations. Rainfall data spanning a period of three years were collected from Nigerian Meteorological Agency (NIMET). The ITU-R P. 618-12 model along with some renowned prediction models were analyzed and their performances with the locally recorded measurement data were compared to establish their suitability or otherwise. The results obtained suggested ITU-R P. 618-12 exhibited the overall best performance at 12 GHz while DAH showed best performance at 26 GHz, even as both models underestimated and overestimated the measurement at Ku and Ka bands respectively. Again, at both frequencies, SST presented the worst performances.